Compact heat exchangers analysis, design and optimization using FEM and CFD approach - Ranganayakulu, C.; Seetharamu, K. N. (Wiley-ASME Press series, 2018)
A comprehensive source of generalized design data for most widely used fin surfaces in CHEs. Compact Heat Exchanger Analysis, Design and Optimization: FEM and CFD Approach brings new concepts of design data generation numerically (which is more cost effective than generic design data) and can be used by design and practicing engineers more effectively. FEM and CFD Approach is ideal for senior undergraduate and graduate students studying equipment design and heat exchanger design.